8. From Thales to Berio: Water as a Common Theme of Philosophy, Physics, and Music - Marisi Rossella (Sciendo, 2016)
Listening to a music piece may trigger memories, give origin to reflections about the physical state of matter, and retrace the development of ancient philosophical thought. This article proposes an interdisciplinary path of active learning - encompassing music education, philosophy, biology, physics, and psychology - which can be realized, choosing an appropriate approach, in both primary and secondary schools.